Analysis of Quality of Service (QoS) Youtube Streaming Video Service in Wireless Network in Faculty of Science and Technology UIN Sunan Kalijaga - Asep Wishnu; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2018)
The growing number of internet users in Indonesia, making the number of users increasing especially video streaming on Youtube service. This increase is based on rapid technological developments, especially PCs, Laptops and Smartphones that use wireless or wireless internet access. The use of streaming video over wireless networks is different from cable networks Because The characteristics of wireless networks are limited Compared to wired networks, and the characteristics of streaming video transmissions that require different handling than traditional text, and the data transmissions. As a first step towards Achieving an optimum Internet network service effort, Applies Action Research This research method by utilizing video quality with 360p, 480p, and 720p. The QOS parameters Analyzed Consist of delay, jitter, throughput, packet loss and bandwidth using wireshark and NetTools for the testing phase. The results of analysis using QoS for streaming video shows the performance of wireless network services at UIN Sunan Kalijaga, Faculty of Science and Technology is still not maximal especially on video with 480p quality, that has a 20 ms delay and jitter quality level ms According -0.0269 to TIPHON is very good. The amount of throughput is 0:55 MBps throughput and the percentage is 3% and the packet loss value is 28%, if it is Categorized by TIPHON standardization bad this value falls into the category. For the average bandwidth used is 329 714 bps value.